Current Status of Malaria Control and Elimination in Africa: Epidemiology, Diagnosis, Treatment, Progress and Challenges - Jiahuan Li; Haragakiza Jean Docile; David Fisher; Khrystyna Pronyuk; Lei Zhao (Springer, 2024)
Abstract The African continent carries the greatest malaria burden in the world. Falciparum malaria especially has long been the leading cause of death in Africa. Climate, economic factors, geographical location, human intervention and unstable security are factors influencing malaria transmission. Due to repeated infections and early interventions, the proportion of clinically atypical malaria or asymptomatic plasmodium carriers has increased significantly, which easily lead to misdiagnosis and missed diagnosis. African countries have made certain progress in malaria control and elimination, including rapid diagnosis of malaria, promotion of mosquito nets and insecticides, intermittent prophylactic treatment in high-risk groups, artemisinin based combination therapies, and the development of vaccines. Between 2000 and 2022, there has been a 40% decrease in malaria incidence and a 60% reduction in mortality rate in the WHO African Region. However, many challenges are emerging in the fight against malaria in Africa, such as climate change, poverty, substandard health services and coverage, increased outdoor transmission and the emergence of new vectors, and the growing threat of resistance to antimalarial drugs and insecticides. Joint prevention and treatment, identifying molecular determinants of resistance, new drug development, expanding seasonal malaria chemo-prevention intervention population, and promoting the vaccination of RTS, S/AS01 and R21/Matrix-M may help to solve the dilemma. China's experience in eliminating malaria is conducive to Africa's malaria prevention and control, and China-Africa cooperation needs to be constantly deepened and advanced. Our review aims to help the global public develop a comprehensive understanding of malaria in Africa, thereby contributing to malaria control and elimination.